Queen Elizabeth II, Duke of Edinburgh at the races with jockey Shane Dye after his Queen's Cup win, Randwick, New South Wales, 1992 - Postle, Bruce, 1940- (1992)
Photograph of Queen Elizabeth II congratulating jockey Shane Dye after he had won the 2000-metre Queen's Cup on the top weight, Aquidity, trained by Tommy Smith. The Duke of Edinburgh looks on--Information supplied by photographer.
Title devised by cataloguer based on information from caption list.
Part of the collection: Bruce Postle collection of photographs, 1963-2007.
Taken while Bruce Postle was a staff photographer for The Age.
Bruce Postle is a Walkley award-winning photojournalist who worked for the Melbourne Age from 1968 to 1996.
Photographer's label on verso.
Also available online
Keywords: Elizabeth -- II, -- Queen of Great Britain, -- 1926-2022 -- Photographs; Philip, -- Prince, consort of Elizabeth II, Queen of Great Britain, -- 1921- -- Portraits; Dye, Shane -- Portraits; Jockeys -- New South Wales -- Randwick -- Portraits; Royal visitors -- New South Wales -- Randwick -- Photographs; Jockeys